Efficiency analysis of sustainable development in Brazil and OECD countries - Camioto, Flávia de Castro; Rodrigues, Isadora Avemir Damaceno (Brazilian Journal of Production Engineering, 2021)
The development of a country is not related to only its economic growth, once its sustainable development should consider social, economic and environmental aspects. This work intends to measure and analyze the efficiency of sustainability in Brazil comparing to other countries of OECD (Organization for Economic and Cooperation Development), understanding the current ambition of Brazil to compose the OECD. This analysis used a mathematical programming method called Data Envelopment Analysis (DEA), which enabled, from the SBM model and the window analysis, to evaluate the ability of countries to reduce the imputs (CO2 emission, energy consumption, unemployment rate and Gini index), as well as to increase the outputs (life expectancy, GDP, sustainable energy, sanitation of quality). The comparison between the countries was made using the sustainable efficiency ranking and the results of this study indicated that the Latvia and Chile is the most eficiente and in the fourth place there is Brazil. Moreover, relative slacks were analyzed and it was concluded that, although Brazil is not a benchmark in any variable, its slacks are relatively low. The index measured is important to contribute to the discussions related to evaluating the countries sustainability, helping to identify those with the best practices with regard to social, economic and environmental aspects; and guide policy decisions regarding government incentives to promote the development of countries in search of more sustainable production.